Kontribusi Ibu Rumah Tangga Pekerja di Desa Nonpertanian dan Desa Pertanian terhadap Pendapatan Keluarga (Studi Kasus di Desa Beraban, Kecamatan Kediri dan Desa Jatiluwih, Kecamatan Penebel, Kabupaten Tabanan) - I DEWA MADE DWI JULIANA PUTRA; DWI PUTRA DARMAWAN; I GUSTI AGUNG AYU LIES ANGGRENI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
The Contribution of Working Wives in Non-agricultural and Agricultural Villages to Family Income (Case Study of Beraban Vilage, Kediri District and Jatiluwih Vilage, Penebel District, Tabanan Regency) The number of dependent family members is one of the main reasons for married women to participate in helping the family economy by working. The purpose is to get additional income. The job opportunities in agricultural villages and non-agricultural villages are certainly different. This causes differences in the level of contribution of income generated by working wives. The purpose of this study is to determine (1) the contribution of working wives in non-agricultural and agricultural villages to household income; (2) working wives motivation to work; (3) the obstacles of working wives at work. This research was conducted from May to July 2020 in Beraban Village, Kediri District, as a non-agricultural village, and in Jatiluwih Village, Penebel District, as an agricultural village. Sampling was done by using the Multistage Random Sampling method with a total sample of 85 people. The data analysis techniques used are quantitative descriptive analysis and qualitative descriptive analysis. The results of the study are (1) the contribution of working wives in non-agricultural villages is bigger than in agricultural villages; (2) the motivation of non-agricultural sector working wives to work is to utilize their spare time, while in the agricultural sector, wives work due to lack of family income; (3) the majority of obstacles for working wives to work in the non-agricultural and agricultural sectors are household duties such as taking care of the house, caring for children, caring for sick family members, and so on.